Opposing needling for analgesia and rehabilitation after unilateral total knee arthroplasty: a randomized, sham-controlled trial protocol - Huang, Hai (Trials, 2020)
BACKGROUND: This randomized controlled clinical trial aims to evaluate the efficacy and safety of opposing needling in patients undergoing unilateral total knee arthroplasty (TKA). Opposing needling is one of the special needling methods used in acupuncture and moxibustion therapy. It involves needling acupoints on the contralateral side for pain management. Although, opposing needling is used for pain management in clinics, evidence to support its effectiveness as an analgesic after total knee arthroplasty is scant. We designed a randomized controlled clinical trial to evaluate efficacy and safety of opposing electroacupuncture (EA) in alleviating pain associated with unilateral total knee arthroplasty. METHODS/DESIGN: This is a protocol for a randomized controlled patient- and assessor-blinded trial with three parallel arms (A, opposing EA; B, operated side EA; C, sham EA). Yinlingquan (SP9), Yanglingquan (GB34), Futu (ST32), and Zusanli (ST36) acupoints are selected for all three groups. In group A, the healthy side will be treated with EA, while the operated side will be administered sham EA. In group B, the operated side will be treated with EA while on the healthy side sham EA will be used. For group C, sham EA will be used on both sides. All patients in the three groups will receive treatment once a day for 3 days. The post-operative pain measured using a visual analogue scale score (including pain while resting and being active) and the additional dose of the patient-controlled analgesic pump after operation will be recorded as the primary outcomes. Secondary outcomes such as knee function and swelling, range of motion (including active and passive range of motion), post-operative anxiety, and acupuncture tolerance will also be assessed. DISCUSSION: Opposing needling is a potential non-pharmacological treatment for relieving pain and improving functional rehabilitation after TKA, during which patients receive acupuncture on the healthy side rather than on the operated side. This sham controlled clinical trial, designed to evaluate efficacy and safety of opposing needling for patients after TKA, will provide evidence for pain management and functional rehabilitation after unilateral TKA. TRIAL REGISTRATION: ChiCTR, ChiCTR1800020297 (http://www.chictr.org.cn/edit.aspx?pid=34231&htm=4). Registered 22 December 2018.